In Search of Social Visibility in Roman Corduba. Identity and social promotion of Publicius Valerius Fortunatus - Clara María Ramos Taboada (Antigüedad y Cristianismo)
The aim of this study is to explore the profile of a promoted individual from the capital of Baetica, the Colonia Patricia Corduba, within the context of a prosopography from below approach. Firstly, an examination of the individual's onomastic profile will be undertaken in greater detail. From a purely superficial perspective and solely based on his nomen, this individual has traditionally been considered as a freedman. Although I endorse this hypothesis, it is necessary to provide an explanation given that conventional views regarding one mere onomastic marker are insufficient. An exhaustive study will be conducted of his onomastic structure and its variation in the two inscriptions he dedicated in Corduba, in order to consistently support this servile origin. Subsequently, this study will address certain questions raised by his onomastics that lead to the possible identification of his social circle. In conclusion, I will conduct a review of his quest for social visibility within the context of freedman euergetism in Hispania.